Teaching Students to Become Self-reflective Practitioners. - Gilbert, Adrienne A. (Therapeutic Recreation Journal)
Teaching Therapeutic Recreation facilitation techniques involve more than teaching students to develop, implement, and evaluate programs. Students usually become proficient in these aspects of programming, but do not gain the competence and confidence to run these programs as therapeutic groups, which requires the ability to process before, during, and following the group. Students need to become aware of potential issues around parallel processing when running groups. This education-based case report summarizes the restructuring and content of a facilitation techniques course. Objectives were added to have students increase competency in self-reflective practice and gain experience in processing. These objectives are achieved through facilitation presentations, role play, and a self-reflection paper in the form of a life story. Course evaluations suggest that this combination of course requirements has helped to develop habits that will encourage self-reflective practice.